Pendampingan pada UMKM Kerupuk 32 dalam Pengajuan Sertifikasi dan Label Halal - Sari, Yudiana; Alhibarsyah, Alhibarsyah; Sundari, Susanti (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
MSME Kerupuk 32 wants to create a competitive advantage so that it can compete to maintain the sustainability of its business by having halal certification and labels issued by BPJPH as the aim of the community service team providing assistance to help carry out the registration process. One of the things that can increase consumer confidence and is a value of excellence is by having recognition of the halalness of cracker products from the government through halal certificates and labels, besides that, because in Indonesia the majority of the population is Muslim, the government must guarantee the halalness of every product circulating in society which is a requirement. The main thing for Muslim consumers to consume food, in this case crackers. This mentoring activity goes through several stages, namely: preparation stage with interviews and observations with partners, document collection stage, account creation stage, data filling stage, data sending stage, validation process stage, inspection stage, halal certificate issuance stage, and certificate submission stage to partners. This mentoring activity ran smoothly and according to targets, and its success was marked by the issuance of a halal certificate which was handed over to partners. This activity can be continued to help MSMEs increase the value of their products in the eyes of consumers or the public so that it is hoped that they can increase sales and income for MSMEs in developing their businesses.